Simulation as a Strategy for Training Cardiopulmonary Resuscitation Skills of Intensive Care Nursing Teams - Carolina de-Sousa, Maria Pereira, Samuel Sousa, Carla Sá-Couto (Journal of the Portuguese Society of Anesthesiology, 2024)
Simulation as a Strategy for Training Cardiopulmonary Resuscitation Skills of Intensive Care Nursing Teams